2017
DOI: 10.5039/agraria.v12i3a5456
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability and minimum number of evaluations for morpho-agronomic characters of elephant-grass for energy purposes

Abstract: Due to the need to promote information relevant to elephant-grass breeding programs for energy purposes, this work aimed to estimate the coefficient of repeatability of the main morpho-agronomic characters and to predict the minimum number of cuts required for selection with greater efficiency. A total of 73 elephant-grass genotypes were evaluated in a randomized block design, in a subdivided plot scheme with two replicates. Nine cuts were performed at six-month intervals, from June 2012 to December 2016, in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The high coefficients of variation (CV) obtained for DMY (37.53%), NT (30.51%), and SD (21.40%) are acceptable, considering that the traits evaluated in this study are quantitative and, consequently, highly influenced by the environment. Gravina et al (2020) and Souza et al (2017) also worked with elephant grass and found similar results regarding CV in experiments evaluating the same quantitative traits.…”
Section: Resultsmentioning
confidence: 62%
“…The high coefficients of variation (CV) obtained for DMY (37.53%), NT (30.51%), and SD (21.40%) are acceptable, considering that the traits evaluated in this study are quantitative and, consequently, highly influenced by the environment. Gravina et al (2020) and Souza et al (2017) also worked with elephant grass and found similar results regarding CV in experiments evaluating the same quantitative traits.…”
Section: Resultsmentioning
confidence: 62%
“…This result was expected since the traits evaluated in this study are controlled by many genes and are highly affected by the growth environment (Souza et al, 2017). However, the form of crop propagation (vegetative) shows an advantage of all genetic variance, whether of an additive, dominant, or epistatic nature (Cruz et al, 2014).…”
Section: Resultsmentioning
confidence: 69%
“…The expression of these traits is complex within this scenario, given the large number of segregating locus controlling the trait, while suffering the influence of environmental effects. Consequently, understanding the heritability and the determining components of their variation are vital in the study of quantitative traits [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%